The Begums of Bhopal : A Dynasty of Women Rulers in Raj India - Khan, Shaharyar M. (London I.B. Tauris, 2000)
This work offers a history of Bhopal, the second largest Muslim state in India, which was reigned over by four Muslim women rulers between 1819 and 1926. It discusses their policies in dealing with the British and provides and account of British Imperial relations with princely states.
Include Index, Bibliography ,Appendix and Glossary
Keywords: Queens -- India--Bhopal -- Kings and rulers